Efficiency of Feed Utilization, Ruminal Traits, and Blood Parameters of Goats Given a Total Mixed Diet Ration Containing Extracted Oil Palm Meal - Pin Chanjula; Sarong So; Chanon Suntara; Rittikeard Prachumchai; Anusorn Cherdthong (Veterinary Sciences, 2022)
This study aimed to evaluate the inclusion levels of extracted oil palm meal (EOPM) from biodiesel byproducts in the total mixed ration (TMR) for goats on feed intake, nutrient digestibility, nitrogen balance, blood parameters, and rumen fermentation characteristics. The EOPM was included at 0%, 10%, 20%, and 30% dry matter (DM) to formulate into four dietary treatments and assigned to goats with an average age of 12 months and an initial body weight of 23 ± 0.5 kg in a 4 × 4 Latin square design. The PROC MIXED procedure was used to analyze all data, and the orthogonal polynomial was tested for EOPM levels using the SAS program. The DM intake, nitrogen, and metabolizable energy linearly (p < 0.05) increased when there was increased EOPM inclusion. Increasing EOPM inclusions resulted in (p < 0.05) a linear increase in fiber digestibility but did not affect DM, crude protein, or ether extract. Total volatile fatty acids increased (p < 0.05) linearly with increasing EOPM inclusions. The EOPM inclusions did not alter the bacteria, fungi, and protozoal populations. Blood parameters were not affected by the inclusions of EOPM except globulin, triglyceride, and MCV concentration. This study revealed that EOPM could be included in up to 20% DM in TMR for goats with no negative impact.